Toxicity of zinc oxide nanoparticles on human skin dermal cells - Maheswaran, H.; Wong, L.S.; Dhanapal, A.C.T.A.; Narendhirakannan, R.T.; Janakiraman, A.K.; Djearamane, S. (Journal of Experimental Biology and Agricultural Sciences (JEBAS), 2021)
Zinc oxide (ZnO) has special physical and chemical characteristics which enable it to be utilized in numerous applications including electronics, sunscreens, pigments, and most notably in biomedical applications. Nanoemulsions containing zinc oxide nanoparticles (ZnO NPs) are progressively sought-after as an active component in cosmetic formulations and are used in sunscreens, moisturizers, and antiaging products. Zinc paste bandages including Unna boot consist of open wove cotton gauze treated with ZnO paste are now common medicaments for leg ulcers. The damaged and broken skins are vulnerable to ZnO NPs uptake. This being the case, ZnO NPs on the skin surface can affect the functions of surrounding cells in numerous ways by penetrating into the skin cells. This could exert toxicity effects on the skin cells over time depending on the concentration and site of ZnO NPs exposure. This review brings together some findings regarding the toxicity of ZnO NPs on human skin dermal cells and thus in turn enlightens the safer usage of ZnO NPs in skin care applications.